2011
DOI: 10.1016/j.jaci.2011.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Invariant natural killer T cells from children with versus without food allergy exhibit differential responsiveness to milk-derived sphingomyelin

Abstract: Background-A key immunological feature of food allergy (FA) is the presence of a T-helper-2 (Th2)-type cytokine bias. Ligation of the invariant natural killer T cell (iNKT) T cell receptor (TCR) by sphingolipids (SL) presented via the CD1d molecule leads to copious secretion of Th2-type cytokines. Major food allergens (e.g. milk, egg) are the richest dietary source of SL (food-SL). Nonetheless, the role of iNKTs in FA is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 42 publications
9
108
0
2
Order By: Relevance
“…Our studies demonstrate reactivity of human iNKT cells to a component of the GlcCer-enriched lipid fraction from human milk, cow's milk, and soy milk. In addition, milk sphingomylein has been reported as antigenic for iNKT cells from some human donors (39). Humans are the only mammal that continues to drink milk past early life, and consumption of milk or other dietary lipid antigens may play an important role in the regulation of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrate reactivity of human iNKT cells to a component of the GlcCer-enriched lipid fraction from human milk, cow's milk, and soy milk. In addition, milk sphingomylein has been reported as antigenic for iNKT cells from some human donors (39). Humans are the only mammal that continues to drink milk past early life, and consumption of milk or other dietary lipid antigens may play an important role in the regulation of immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…INKTs specifically recognize self and foreign lipids, including food-derived ones, via their semi-invariant T cell receptor (TCR) [72,73]. Jyonouchi et al showed that iNKTs produce IL-4 and IL-13 upon stimulation with milk-derived lipids and are recruited at the esophagus via RANTES [38].…”
Section: Pathogenesismentioning
confidence: 99%
“…These include bacteria, fungi, protozoa and metazoa that either colonize the mucosa (true or facultative commensals, opportunistic pathogens), or temporarily present themselves at the mucosa following ingestion or inhalation (commensals, pathogens, environmental antigens) ( Table 1). Besides microbes, environmental antigens 64 could be derived from food components too, like milk lipids, 95,96 and from airborne pollen, 83 either directly or after processing by the commensals. Furthermore, microbe-induced changes in the presentation of hostderived self-lipids or the expression levels of CD1d itself could conceivably modulate mucosal iNKT cell responses as well.…”
Section: Discussionmentioning
confidence: 99%